The relationships between institutional environment and guardian involvement on the academic achievement and learning motivation of children reared in a Malaysian orphanage - Alfred Thananathan, Aneesha Jeyanthi; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This research was conducted to study the relationships between academic performance and learning motivation with institutionalised environments and guardian involvement of children reared in a Malaysian orphanage. This study involves 50 students consisting of 21 female and 29 male students. These students are in secondary school with ages ranging from 13-17 years old. This study was conducted in a home for orphans and under-privileged children and all the participants of this study are from this home. The findings of this study hopes to show that there will be a significant relationship between academic achievement and learning motivation with guardian involvement and institutional environment providing further implications on how the home environment affects children’s’ academic and learning motivation outcomes.